Perioperative Myocardial Injury/Infarction After Non-cardiac Surgery in Elderly Patients - Gao, Linggen; Chen, Lei; He, Jing; Wang, Bin; Liu, Chaoyang; Wang, Rong; Fan, Li; Cheng, Rui (Frontiers in Cardiovascular Medicine, 2022)
At present, we have entered an aging society. Many diseases suffered by the elderly, such as malignant tumors, cardiovascular diseases, fractures, surgical emergencies and so on, need surgical intervention. With the improvement of Geriatrics, surgical minimally invasive technology and anesthesia level, more and more elderly patients can safely undergo surgery. Elderly surgical patients are often complicated with a variety of chronic diseases, and the risk of postoperative myocardial injury/infarction (PMI) is high. PMI is considered to be the increase of cardiac troponin caused by perioperative ischemia, which mostly occurs during operation or within 30 days after operation, which can increase the risk of short-term and long-term death. Therefore, it is suggested to screen troponin in elderly patients during perioperative period, timely identify patients with postoperative myocardial injury and give appropriate treatment, so as to improve the prognosis. The pathophysiological mechanism of PMI is mainly due to the increase of myocardial oxygen consumption and / the decrease of myocardial oxygen supply. Preoperative and postoperative risk factors of myocardial injury can be induced by mismatch of preoperative and postoperative oxygen supply. The treatment strategy should first control the risk factors and use the drugs recommended in the guidelines for treatment. Application of cardiovascular drugs, such as antiplatelet β- Receptor blockers, statins and angiotensin converting enzyme inhibitors can effectively improve postoperative myocardial ischemia. However, the risk of perioperative bleeding should be fully considered before using antiplatelet and anticoagulant drugs. This review is intended to describe the epidemiology, diagnosis, pathophysiology, risk factors, prognosis and treatment of postoperative myocardial infarction /injury.